Influence of trainings loadings of different primary orientation on correction of the psychofisiological state of young sportsmen - Воропай [Sergiy Voropay] Сергій Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
The comparative analysis of efficiency of influence of the trainings loadings of different overwhelming orientation is conducted on the level of display of the psychofisiological state of young bicyclists 13–16 years. 15 young bicyclists took part in research. The program of researches was made taking into account character of motive activity. Overwhelming orientation of the training loading on «undercutting of backward» and on development of «profiling» qualities and capabilities. A pedagogical experiment was conducted the method of «cross study». Certainly more effective at the correction of the psychofisiological state of young bicyclists 13–16 years influence of the trainings loadings of the «profiling» qualities and capabilities directed on overwhelming development.